Analysis of Student's Misconceptions in The Subject Material Circle in View of Learning Readiness and Student's Think Style - Wardani, Endang Purwati; Fantaye, Abayneh Kebede; Ade, Jimoh Azeez (Cahaya Ilmu Cendekia Publisher, 2023)
The aims of this study were: (1) to find out the characteristics of misconceptions, and (2) to find out the causes of misconceptions in class XI students in the 2013/2014 academic year on the equation of a circle and the equation of a tangent line. circle seen from the readiness and learning styles of students. Qualitative research was applied in this research. The research subjects were eleventh grade students of SMA Negeri 3 Surakarta. Data sources were taken from informants (students), documentation (questionnaire), and tests. Data collection was carried out using interviews, diagnostic tests, and questionnaires. Data validity uses source triangulation. Data analysis uses the concept of Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions.